(untitled) (Brazilian Journal of Radiation Sciences, 2022)
The conservative surgery for impalpable breast cancer requires an intraoperative localization method that guides the identification and correct excision of the lesion. The aim of this study is to comparatively analyze two intraoperative breast localization technologies, wire guided localization (WGL) and radioactive seed localization (RSL), regarding their surgical efficacy through the outcomes of surgical margins, intraoperative re-excision, reoperation and recurrence. To this end, a systematic search was realized in databases for clinical trials that match with the study eligibility criteria. The selected studies were evaluated for their methodological quality; the data were then collected and quantitatively synthesized. The results comprised thirty-eight studies that match the eligibility criteria. The main outcomes reported demonstrating that the RSL is at least equivalent to the WGL in efficiency rates. These results confirm the method applicability for impalpable breast lesions surgery in an effective way, in addition to presenting organizational optimization of radiology and surgery services by allowing the surgery to be performed up to two months after seed implantation.